Influência das ferramentas de CAD em um projeto aeronáutico - Oliveira, Luiz Gustavo Fernandes Santiago de (2018)
It’s know that CAD is used on an aircraft design, but to understand when and how they are used it’s not an easy task, mostly because they are directly involved in the development time. When comes to project efficiency, knowledge on these tools and how the CAD team work are essential. Using the software CATIA, two airplanes were created as the specifications from AIAA suggested, also the parts from these aircraft were used in structural and aerodynamics analysis. The results have shown that these tools are crucial for a better project development, so it is confirmed that use of CATIA on an aircraft design are vital and are responsible for most part of it.